Efectos del entrenamiento con sobrecargas isoinerciales sobre la función muscular - Mosteiro-Munoz, F.; Dominguez, R. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2017)
Resistance training should be included in all exercise programmes which improve health and quality of live. These programmes have been focusing on both concentric-eccentric contractions, however, a new type of resistance training based on eccentric contractions provided by inertial overload is being carried out. Therefore, the aim of the present study is to prove the effects of this kind of training based on eccentric contractions by inertial overload. Databases utilized to carry out information research were Web of Science, Pubmed, Medline, Dialnetand Scielo. Results would suggest that inertial training based on inertial overload produces maximal EMG and an earlier muscular hypertrophy compared to conventional resistance training, besides the fact it could have successful on muscle-tendon injuries.